Pengayaan Materi Matematika Bagi Siswa Kelas 3 di SD Negeri 040457 Berastagi - Mariana Surbakti; Paten Surbakti; Elda Sihaloho; Jelita Karo Sekali (LPPM Universitas HKBP Nommensen, 2023)
The purpose of this service activity is to provide enrichment of math material for grade 3 students who support in solving elementary math problems, and provide training in working on elementary math problems. This service activity lasts for a month and is carried out after school hours are finished. Free tutoring activities are carried out with the aim of teaching students to be able to overcome the problem of decreased interest in learning and low ability of students in mathematics, due to the length of the online learning process due to the Covid-19 pandemic. The community service team carried out PKM activities at SD Negeri 040457 Berastagi from February 2 2022 to February 26 2022, every Tuesday to Friday for one and a half hours. This service activity is carried out with an emphasis on strategies for working on short questions and description questions. Evaluation of the implementation of activities is carried out by holding a free test / giving questions to work on before the activity and the post test is retested after the activity. The learning process is carried out with guidance in small classes and using learning media such as lists of numbers, addition tables, multiplication tables, etc. to attract students' interest. The results of the activity showed an increase in students' interest in learning and math skills up to 75%. This proves that students can be more enthusiastic about learning if mentoring and direct interaction are provided.